PENERAPAN TEORI DAN KEBIJAKAN KRIMINAL DALAM PERTIMBANGAN HUKUM DALAM SISTEM PERADILAN PIDANA - IDA RAHMA (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2018)
The function of criminal law aims to prevent future crimes in order to prevent the occurrence of criminal countermeasures. The criminal itself is a sanction or a sorrow that tells. Criminal law is a rule of law or a set of rules or legal norms that regulate an act which is a criminal act, when an act is declared as a criminal act and set the effect (witness) given in reaction to the act that violates the rule of criminal law. The function of the criminal law itself is to provide a criminal to those who violate the penal law through state equipment, in order to maintain public order. Law enforcement is the activity of harmonizing relationships of values that are outlined in the rules and attitude of acts as a series of the final value of the termination to create as social enginering, maintaining and maintaining as the social control of social interaction, whether it is a preventive action (preventive) ) As well as acts of eradication (repressive)